Acidification of the Nordic Seas - Fransner, Sara Filippa Krusmynta; Fröb, Friederike; Tjiputra, Jerry; Goris, Nadine; Lauvset, Siv Kari; Skjelvan, Ingunn; Jeansson, Emil; Omar, Abdirahman; Chierici, Melissa; Jones, Elizabeth Marie; Fransson, Agneta; Olafsdóttir, Solveig R.; et al. (Biogeosciences, 2022)
Due to low calcium carbonate saturation states, and winter mixing that brings anthropogenic carbon to the deep ocean, the Nordic Seas and their cold-water corals are vulnerable to ocean acidification. Here, we present a detailed investigation of the changes in pH and aragonite saturation in the Nordic Seas from preindustrial times to 2100, by using in situ observations, gridded climatological data, and projections for three different future scenarios with the Norwegian Earth System Model (NorESM1-ME). During the period of regular ocean biogeochemistry observations from 1981–2019, the pH decreased with rates of 2–3 × 10−3 yr−1 in the upper 200 m of the Nordic Seas. In some regions, the pH decrease can be detected down to 2000 m depth. This resulted in a decrease in the aragonite saturation state, which is now close to undersaturation in the depth layer of 1000–2000 m. The model simulations suggest that the pH of the Nordic Seas will decrease at an overall faster rate than the global ocean from the preindustrial era to 2100, bringing the Nordic Seas' pH closer to the global average. In the esmRCP8.5 scenario, the whole water column is projected to be undersaturated with respect to aragonite at the end of the 21st century, thereby endangering all cold-water corals of the Nordic Seas. In the esmRCP4.5 scenario, the deepest cold-water coral reefs are projected to be exposed to undersaturation. Exposure of all cold-water corals to corrosive waters can only be avoided with marginal under the esmRCP2.6 scenario. Over all timescales, the main driver of the pH drop is the increase in dissolved inorganic carbon (CT) caused by the raising anthropogenic CO2, followed by the temperature increase. Thermodynamic salinity effects are of secondary importance. We find substantial changes in total alkalinity (AT) and CT as a result of the salinification, or decreased freshwater content, of the Atlantic water during all time periods, and as a result of an increased freshwater export in polar waters in past and future scenarios. ...